The association between systemic immune inflammation index and disease activity in patients with rheumatoid arthritis - Anahita Amirpour; Rana Irilouzadian; Hediyeh Baghsheikhi; Maryam Armanfar; Toktam Alirezaei (Romanian Journal of Rheumatology)
Background. Novel blood-derived indices are a potential substitute for traditional inflammatory markers which have disputable correlations and clinical applications in different immunological diseases. Hereby, we aimed to reveal the association of neutrophil-to-lymphocyte ratio (NLR), platelet-to-lymphocyte ratio (PLR), and systemic immuneinflammation index (SII) with disease activity score (DAS28) and clinically active disease according to simple disease activity index (SDAI). Methods. We included 250 patients and they were grouped equally based on SDAI into two groups of patients in remission and with active disease. A blood sample was drawn from our patients to measure NLR, PLR, SII, rheumatoid factor, erythrocyte sedimentation rate (ESR), and C-reactive protein (CRP). Independent samples t-tests, chi-square, and Mann-Whitney U test were used accordingly. Logistic regression evaluated the factors that affect active RA. Results. PLR, DAS28, rheumatoid factor, quantitative and qualitative ESR and CRP had a significant difference between patients with active RA and in remission. SII had significant correlation with DAS28 but PLR and NLR were not correlated with DAS28. Also, PLR was the only index to be correlated with clinically active disease based on SDAI. The logistic regression showed that NLR, SII, ESR, and CRP were independent factors predicting active RA. Conclusion. We demonstrated that SII was significantly correlated with DAS28 and PLR was correlated with active RA. NLR, SII, CRP, and ESR were independent risk factors for RA flare-ups.